Kadar Serat, Aktivitas Antioksidan, Karakteristik Fisik Dan Sensoris Yoghurt Susu Kecambah Kedelai Dengan Penambahan Ekstrak Cincau Hijau - Nurur Rizqi Penta Amalia; siti aminah (Jurnal Pangan dan Gizi, 2021)
Fermented soybean sprouted milk (yogurt) has components that play a role in health. The physical and functional characteristics of soybean sprouted milk yogurt can be improved by the addition of local ingredients, including green grass leaf. This study aims to determine the effect of adding green grass leaf extract on fiber content, antioxidant activity,  the physical and sensory characteristics of soybean sprouted yogurt. The research design used a completely randomized design (CRD) with 4 treatments, namely the proportion of addition of grass  leaf extract: 1, 3, 5, and 7 percent and 1 control without the addition of love leaf extract. Repetitions were carried out 5 times. Analyzes were carried out on the levels of fiber, antioxidants, physical characteristics (pH and viscosity) and sensory (color, aroma, taste and consistency) of yogurt. The results showed that the addition of green grass jelly leaf extract to soybean sprouted milk yogurt had an effect on fiber content, antioxidant activity and physical characteristics (pH and viscosity) but green did not affect sensory characteristics.